Direct Interaction of Selenoprotein R with Clusterin and Its Possible Role in Alzheimer's Disease. - Ping Chen; Chao Wang; Xiaojie Ma; Yizhe Zhang; Qing Liu; Shi Qiu; Qiong Liu; Jing Tian; Jiazuan Ni (PLoS ONE, 2013)
Selenoprotein R (SelR) plays an important role in maintaining intracellular redox balance by reducing the R-form of methionine sulfoxide to methionine. As SelR is highly expressed in brain and closely related to Alzheimer's disease (AD), its biological functions in human brain become a research focus. In this paper, the selenocysteine-coding TGA of SelR gene was mutated to cysteine-coding TGC and used to screen the human fetal brain cDNA library with a yeast two-hybrid system. Our results demonstrated that SelR interacts with clusterin (Clu), a chaperone protein. This protein interaction was further verified by fluorescence resonance energy transfer (FRET), coimmunoprecipitation (co-IP), and pull-down assays. The interacting domain of Clu was determined by co-IP to be a dynamic, molten globule structure spanning amino acids 315 to 381 with an amphipathic-helix. The interacting domain of SelR was investigated by gene manipulation, ligand replacement, protein over-expression, and enzyme activity measurement to be a tetrahedral complex consisting of a zinc ion binding with four Cys residues. Study on the mutual effect of SelR and Clu showed synergic property between the two proteins. Cell transfection with SelR gene increased the expression of Clu, while cell transfection with Clu promoted the enzyme activity of SelR. Co-overexpression of SelR and Clu in N2aSW cells, an AD model cell line, significantly decreased the level of intracellular reactive oxygen species. Furthermore, FRET and co-IP assays demonstrated that Clu interacted with β-amyloid peptide, a pathological protein of AD, which suggested a potential effect of SelR and Aβ with the aid of Clu. The interaction between SelR and Clu provides a novel avenue for further study on the mechanism of SelR in AD prevention.